2013
DOI: 10.1002/jmv.23708
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus detection and cytokine levels (IL‐10, IL‐6, and IFN‐γ) in ocular fluid from Tunisian immunocompetent patients with uveitis

Abstract: Human herpesviruses (HHVs) are involved in the pathogenesis of different types of uveitis. Cytokine response plays an important role in virus-induced immunopathology. This study aimed to investigate the incidence of HHVs in aqueous humor samples of immunocompetent patients with suspected viral uveitis and cytokine (IL-10, IL-6, and IFN-γ) expression profiling. Forty-seven aqueous humor samples were collected from immunocompetent patients with viral uveitis. Samples were assayed for HHV-1 to HHV-8 by in-house r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 61 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…Although expensive and requiring greater technical expertise and resources, PCR tests, whether quantitative or qualitative, show superior sensitivity and specificity compared to antibody detection tests [ 27 ]. Of the eight studies that used PCR, three were quantitative [ 28 30 ], two qualitative [ 31 , 32 ], and the remaining three did not specify if the PCR used was quantitative or qualitative [ 33 – 35 ]. Four of the eight studies were performed on CSF (in patients that presented with signs of central nervous system [CNS] infections), whereas two studies were performed on ocular fluids (mostly from patients with uveitis).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although expensive and requiring greater technical expertise and resources, PCR tests, whether quantitative or qualitative, show superior sensitivity and specificity compared to antibody detection tests [ 27 ]. Of the eight studies that used PCR, three were quantitative [ 28 30 ], two qualitative [ 31 , 32 ], and the remaining three did not specify if the PCR used was quantitative or qualitative [ 33 – 35 ]. Four of the eight studies were performed on CSF (in patients that presented with signs of central nervous system [CNS] infections), whereas two studies were performed on ocular fluids (mostly from patients with uveitis).…”
Section: Resultsmentioning
confidence: 99%
“…The patients were highly immunosuppressed (median CD4 count was 89) and the case fatality rate for VZV CNS infections was 30.8% [ 32 ] [Siddiqi, personal communication, 13 October 2016]. In immunocompetent patients in Tunisia, 29.8% of uveitis cases were caused by VZV [ 30 ], while in South Africa, 32% of uveitis cases were caused by VZV [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nahdi et al from Tunisia also reported that EBV DNA was positive in 19% (4/21) of the patients with uveitis, as determined by PCR of the vitreous fluid (21). These results suggest that the detection of EBV DNA in the vitreous fluid may not be rare in uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…The AH of immunocompetent patients with HCMV anterior segment infections was reported to have significantly higher levels of IL-5, IL-6, IL-8 (CXCL8), monocyte chemotactic protein-1 (MCP-1; CCL-2), macrophage inhibitory protein-1β (MIP-1β; CCL-4), granulocyte colony stimulating factor, and transforming growth factor-β, but low levels of IL-2, IL-12, TNF-α, and INF-γ compared to the control groups. 48,49 Interestingly, no significant difference in aqueous cytokines was detected in HCMV qPCR-positive immunocompetent PSS patients when compared to HCMV qPCR-negative PSS patients. 49 Future studies are warranted to provide better insights into the inflammatory response or intraocular milieu that may potentiate HCMV anterior segment infection.…”
Section: Anterior Uveitismentioning
confidence: 91%